An Interoceptive Predictive Coding Model of Conscious Presence - Seth, Anil K.; Suzuki, Keisuke; Critchley, Hugo D. (Frontiers in Psychology, 2012)
We describe a theoretical model of the neurocognitive mechanisms underlying conscious presence. The model is based on interoceptive prediction error and is informed by predictive models of agency, general models of hierarchical predictive coding and dopaminergic signalling in cortex, the role of the anterior insular cortex in interoception and emotion, and cognitive neuroscience evidence from studies of virtual reality and of psychiatric disorders of presence, specifically depersonalization/derealization disorder. The model associates presence with successful ‘explaining away’ by top-down predictions of informative interoceptive signals evoked by autonomic control signals and, indirectly, by visceral responses to afferent sensory signals. The model connects presence to agency by allowing that predicted interoceptive signals will depend on whether afferent sensory signals are determined, by a parallel predictive-coding mechanism, to be self-generated or externally caused. Anatomically, we identify the anterior insular cortex as the likely locus of key neural comparator mechanisms. Our model integrates a broad range of previously disparate evidence, makes predictions for conjoint manipulations of agency and presence, offers a new view of emotion as interoceptive inference, and represents a step towards a mechanistic account of a fundamental phenomenological property of consciousness.